A COMPARSION SURVEY PAPER ON BLOCKCHAIN TECHNOLOGY, BITCOIN AND ETHEREUM - P, Ashok.; R, Lavanya.; V, Vidhya; K, Karthick.; Sanjarkhan, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The blockchain technology is a main approach in the field of Information technologies. Satoshi Nakamoto’s development of Bitcoin in 2008 has often greeted as a radical development in money and being the first example of a digital asset which simultaneously has no centralized issuer or controller. In cryptocurrency, bitcoin has gained a lot of attention. Alternative applications of blockchain technology using blockchain digital assets to represent custom currency and financial instruments as well as more complex applications having digital assets being directly controlled by a piece of code implementing smart contracts (Arbitrary rules). Ethereum intends to provide is a blockchain with a built in fully fledged turing complete programming language that can be used to create “contracts” that can be used to encode arbitrary state transaction function, simply by writing up the logic in a few lines of code. Together with Ethereum, blockchain implementation with focus on smart contracts. Ethereum represents the very core of modern cryptocurrency development.